Proceedings of the 41st ACM Technical Symposium on Computer Science Education 2010
DOI: 10.1145/1734263.1734348
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of pairing by ability

Abstract: An analysis of data from 259 CS1 students is performed to compare the performance of students who were paired by demonstrated ability to that of students who were paired randomly or worked alone. The results suggest that when given individual programming tasks to complete, lowestquartile students who were paired by ability perform better than those who were paired randomly and those who worked alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 18 publications
3
21
0
1
Order By: Relevance
“…The student's skill level is the most accurate predictor of the partner compatibility [18] in PP. Out of these factors, we believe that gender and academic achievement level of the other partner are significant factors [11]. As per Theodore, V.T.…”
Section: Personality Conflictsmentioning
confidence: 74%
“…The student's skill level is the most accurate predictor of the partner compatibility [18] in PP. Out of these factors, we believe that gender and academic achievement level of the other partner are significant factors [11]. As per Theodore, V.T.…”
Section: Personality Conflictsmentioning
confidence: 74%
“…In addition, weaker students see that they are not alone in the difficulties that they are experiencing and thus may be less likely to become hopelessly discouraged. Our intuition on this issue has been strengthened by the experiences of several colleagues who taught our course using random pairing before switching to pairing by ability [Braught et al 2010]. …”
Section: Instructor Observationsmentioning
confidence: 99%
“…Pair programming has become a popular collaboration technique for research in computer science education and many studies have shown positive results (e.g., [1][7][8] [14]). Pair programming is the technique whereby two students work together, using a single computer.…”
Section: Previous Researchmentioning
confidence: 99%
“…(These goals were recommended by [4] but other research [1] found that students from the lowest quartile were most successful if they pair-programmed with another student from the lowest quartile. )…”
Section: Group Projectsmentioning
confidence: 99%